Correlation between diet and gut bacteria in a population of young adults. (18th May 2016) - Mayorga Reyes, Lino; González Vázquez, Raquel; Cruz Arroyo, Schahrasad M.; Melendez Avalos, Araceli; Reyes Castillo, Pedro A.; Chavaro Pérez, David A.; Ramos Terrones, Idalia; Ramos Ibáñez, Norma; Rodríguez Magallanes, Magdalena M.; Langella, Philippe; Bermúdez Humarán, Luis; Azaola Espinosa, Alejandro
Abstract: Dietary habits strongly influence gut microbiota. The aim of this study was to compare and correlated the abundance of Firmicutes and Bacteroidetes phyla, some representative bacteria of these phyla such as Bacteroides thetaiotaomicron, Prevotella, Faecalibacterium prausnitzii, Clostridium leptum and Bifidobacterium longum as a member of Actinobacteria phylum in young adults with their food intake. Faecal samples used came from lean subjects (BMI = 19.83 ± 0.94 kg/m 2 ), overweight (BMI = 27.17 ± 0.51 kg/m 2 ) and obese (BMI = 41.33 ± 5.25 kg/m 2 ). There were significant differences in total studied gut microbiota between the overweight and lean groups. Members of the Firmicutes phylum, and Bifidobacterium longum, were more abundant in the lean group. The results suggest that diet rich in unsaturated fatty acids and fibre promote an abundant population of beneficial bacteria such as B. longum and Bacteroidetes. However, it has been considered that the results may be biased due to the size of the individuals studied; therefore the results could be only valid for the studied population.